Wind effect in short-range putting - Suzuki, T.; Asai, T.; Kita, T. (International Journal of Golf Science, 2025)
In this study, we investigated the effects of wind on the stopping position of a ball while putting on a green. The experiment was conducted indoors on artificial turf, and the ball was set to stop at the target in the absence of wind. The target distance was set at 3 meters, and the green speed was 12 feet as measured by a stimpmeter. Subsequently, a fan was used to generate wind at speeds of 2 and 4 m/s at a height of 5 cm above the ground. The results showed that the crosswind (right-to-left) caused the ball to stop at -17.0 ± 2.5 cm to the left of the target at 2 m/s and -35.8 ± 5.7 cm to the left of the target at 4 m/s, resulting in a directional error. In the headwind at 2 m/s, the ball stopped at -28.0 ± 9.1 cm, and at 4 m/s, it stopped at -41.8 ± 9.8 cm in front of the target. In a tailwind at 2 m/s, it stopped 31.0 ± 8.8 cm, and at 4 m/s, it stopped 65.5 ± 7.2 cm behind the target, resulting in distance errors. These results clearly show that wind affects the stopping position of the ball, with asymmetric distance errors observed for tailwind and headwind, even at the same wind speed. The increased distance should be noted when the wind is a tailwind. These results could be applied not only for putting green readings in actual golf competitions but also for algorithms simulating golf and screen golf, with a focus on enhancing realism.